If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6u + -1(2u + -4) * 7 = 3 Reorder the terms: 6u + -1(-4 + 2u) * 7 = 3 Reorder the terms for easier multiplication: 6u + -1 * 7(-4 + 2u) = 3 Multiply -1 * 7 6u + -7(-4 + 2u) = 3 6u + (-4 * -7 + 2u * -7) = 3 6u + (28 + -14u) = 3 Reorder the terms: 28 + 6u + -14u = 3 Combine like terms: 6u + -14u = -8u 28 + -8u = 3 Solving 28 + -8u = 3 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -8u = 3 + -28 Combine like terms: 28 + -28 = 0 0 + -8u = 3 + -28 -8u = 3 + -28 Combine like terms: 3 + -28 = -25 -8u = -25 Divide each side by '-8'. u = 3.125 Simplifying u = 3.125
| 6(16-4y)=72 | | 5(x-4)-4(x+1)=0 | | 10x-5=9x+8 | | (8x+2)(9x+3)+x=180 | | (8x+2)(9x+3)+x=q | | 5-.66666666n=7 | | 64-7x=11x+18 | | 2x+2=40 | | 8log(x+3)=10 | | 1-3x+8x=3+5x | | 4x+-2=6 | | -16y=0 | | 3(m-9)= | | 3x(x-12)=0 | | (x^2-x+.25)=(.3+x) | | 8-4(m+5)= | | X+2=3x+2-2x | | a^4-12a^2+35=0 | | 6a(2a-1)-(3a^2-3a)= | | -8x=4 | | n-15=30 | | -30-5m=-4(m+7) | | 8x^2-11x+3=0 | | 27=17-2y | | -2=2x+10 | | 26+4a=6a | | 35x^2+56x+21=0 | | 4s=76 | | 10x-3(x-6)=11+30 | | x^2+y^2-2x+14y+14=0 | | C=0.4t+1 | | 3(x+2)-5=10x-3 |